2022
DOI: 10.1002/ctm2.1071
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐derived extracellular vesicles regulate follicular activation and improve ovarian function in old mice by modulating local environment

Abstract: In mammals, ovarian function is dependent on the primordial follicle pool and the rate of primordial follicle activation determines a female's reproductive lifespan. Ovarian ageing is characterised by chronic low‐grade inflammation with accelerated depletion of primordial follicles and deterioration of oocyte quality. Macrophages (Mφs) play critical roles in multiple aspects of ovarian functions; however, it remains unclear whether Mφs modulate the primordial follicle pool and what is their role in ovarian age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…The prolonged presence of senescent cells in the tissue is problematic because they secrete SASPs that trigger local inflammation and spread the senescence phenotype 31 . Numerous studies have associated ovarian aging with a chronic low-grade inflammatory environment 12 , 32 , 33 , supported by our findings demonstrating the activation of inflammation-associated signal pathways (NF-κB, NOD-like receptor, IL-17 and FoxO) and increased expression of pro-inflammatory factors (such as IL-1α, IL-1β, IL-6, IL-8, TNF and IFNγ) in aged ovaries. This inflammatory microenvironment in the ovary may induce oocyte damage, as indicated by the activation of the DNA damage system in aged oocytes, suggesting chronic inflammation as a potential confounding factor in ovarian aging.…”
Section: Discussionsupporting
confidence: 85%
“…The prolonged presence of senescent cells in the tissue is problematic because they secrete SASPs that trigger local inflammation and spread the senescence phenotype 31 . Numerous studies have associated ovarian aging with a chronic low-grade inflammatory environment 12 , 32 , 33 , supported by our findings demonstrating the activation of inflammation-associated signal pathways (NF-κB, NOD-like receptor, IL-17 and FoxO) and increased expression of pro-inflammatory factors (such as IL-1α, IL-1β, IL-6, IL-8, TNF and IFNγ) in aged ovaries. This inflammatory microenvironment in the ovary may induce oocyte damage, as indicated by the activation of the DNA damage system in aged oocytes, suggesting chronic inflammation as a potential confounding factor in ovarian aging.…”
Section: Discussionsupporting
confidence: 85%
“…Recent research has demonstrated that miR-99a-5p, a specific miRNA released by M2 macrophages, plays a vital part in ameliorating the inflammatory microenvironment and combating aging [ 34 ]. Additionally, miR-99a-5p is believed to possess inhibitory effects on atherosclerosis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, the regulation of FLT1 by miRNA‐10b‐5p is scarce in folliculogenesis, which should be researched in the future. It was found that macrophage‐derived exosomes containing miRNA‐99a‐5p and miRNA‐107 regulate the dormancy and activation of follicles through the PI3K/mTOR signaling pathway, which plays a decisive role in the opening of folliculogenesis (Xiao et al, 2022). At the same time, the expression level of miRNA‐21‐5p is highly correlated not only with blastocyst development and oocyte euploid rate, but also with follicular atresia (Bartolucci et al, 2020; Donadeu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%